Specificity of Sports League Marketing (Laisvalaikio tyrimai, 2018)
In this article, the specifics of a special type of a sports organization – sports league as subject and object of marketing – are considered. During the conducted research, the author defined the main features and characteristics of professional and amateur leagues, formulated their marketing functions and tasks. On the basis of the analysis of the Russian, European and American leagues, their classification by the signs important for practical marketing is developed. The objects of marketing and the marketing environment of sports leagues of various types are defined. Sports leagues are represented by a special type of sports organizations which changed the shape of sports industry. A large number of the leagues which arose in recent years in the world require their classification and a careful analysis of activities for the development of effective marketing solutions. Object of a research: marketing activity of sports leagues. A research purpose: establishment of the specifics of the use of marketing by the management of leagues. Methods. During the research, methods of the analysis of documents, an axiomatic method, hypothetical-deductive and inductive methods, and also, the ascension method from abstract to specific is used. Conclusions and prospects: 1. The main specifics of marketing of sports league are based on the characteristics of its main market product – a sports tournament. 2. Popularity of such model of a sports organization as league is determined by its opportunities of the most effective holding of sports events due to concentration of marketing competences and their system. 3. Modern sports leagues perform three main functions: organizational, marketing and financial. 4. Marketing of a sports league has the features depending on its type. It is reasonable to allocate 18 types of leagues by six criteria. 5. An important task of management of a sports league is the correct determination of objects of marketing and carrying out the analysis of the marketing environment.Keywords: sports marketing, leagues, marketing environment, competition, marketing products.